2017
DOI: 10.15421/021736
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between lipid exchange and thyroid status in the conditions of prolonged influence of small doses of radiation

Abstract: We studied the interaction between the indicators of lipid exchange and thyroid status among the inhabitants of radiation contaminated territories under additional psycho-emotional load. We observed 170 students aged between 18–24 and divided them into a control group of students who were from areas unaffected by radiation (70 people) and the main experimental group of students from territories of increased radio-ecological load (IV radiation zone, 100 people). We determined the content of thyrotropic hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The level of LDL-C inversely correlated with the level of triiodothyronine; in the subgroup of hyperthyroidism, this correlation was positive. In all three subgroups, a statistically significant correlation between the level of LDL-C and the level of oxidative processes stimulator TSH (Sokolenko & Sokolenko, 2017), was noted. Thus, thyroid status had a significant effect on the lipid metabolism of the examined patients, although its role was leveled to some extent in conditions of emotional stress.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The level of LDL-C inversely correlated with the level of triiodothyronine; in the subgroup of hyperthyroidism, this correlation was positive. In all three subgroups, a statistically significant correlation between the level of LDL-C and the level of oxidative processes stimulator TSH (Sokolenko & Sokolenko, 2017), was noted. Thus, thyroid status had a significant effect on the lipid metabolism of the examined patients, although its role was leveled to some extent in conditions of emotional stress.…”
Section: Discussionmentioning
confidence: 77%
“…We have shown that the inhabitants of the territory of enhanced radioecological control demonstrated a certain tension of the thyroid system, which was characterized by high TSH concentration in people with a high T 3 level in peripheral blood. The thyroid status correlated with lipid parameters (Sokolenko & Sokolenko, 2017). Also, in this cohort radiation-induced intensification of oxidative processes was detected, which grew under conditions of additional stress of emotional nature and influenced the immune system (Sokolenko et al, 2018).…”
Section: Introductionmentioning
confidence: 64%
“…In our previous studies, typical signs of stress reactions among individuals aged 18-24 years old who lived on the territory of enhanced radiation control were marked, in particular, raised level of cortisol (Sokolenko & Sokolenko, 2015), which increased further in conditions of additional psycho-emotional stress (Sokolenko, 2015). As a result, signs of immunosuppression were observed in this group, which were accompanied by an imbalance of thyroid status and lipid metabolism, changes in oxidative and antioxidant activity (Sokolenko & Sokolenko, 2015, 2017a2017b;Sokolenko 2016).…”
Section: Introductionmentioning
confidence: 77%
“…Oxidative damage correlates with the level of cholesterol of low density lipoprotein (Hs-LDL) and triglycerides (Fernández-Sánchez et al, 2011). Indeed, we have already shown that the level of total cholesterol and Hc-LDL was increased in the experimental group, and so, the level of Hc-LDL positively correlated with the number of stab neurotrophils (Sokolenko, 2016;Sokolenko & Sokolenko, 2017a). This may indicate stimulated by hypercholesterolemia activation in the development of neutrophils in the bone marrow and spleen, which, in turn, creates preconditions for the development of inflammatory reactions (Tall & Yvan-Charvet, 2015).…”
Section: Correlation Coefficientmentioning
confidence: 97%
See 1 more Smart Citation